Quercetin protects HCT116 cells from Dichlorvos-induced oxidative stress and apoptosis - Ben Salem, Intidhar (Cell Stress Chaperones, 2015)
The present study was designed to assess the possible protective effects of Quercetin (QUER), a flavonoid with well-known pharmacological effects, against Dichlorvos (DDVP)-induced toxicity in vitro using HCT116 cells. The cytotoxicity was monitored by cell viability, reactive oxygen species (ROS) generation, anti-oxidant enzyme activities, malondialdehyde (MDA) production, and DNA fragmentation. The apoptosis was assessed through the measurement of the mitochondrial transmembrane potential (ΔΨm) and caspase activation. The results indicated that pretreatment of HCT116 cells with QUER, 2 h prior to DDVP exposure, significantly decreased the DDVP-induced cell death, inhibited the ROS generation, modulated the activities of catalase (CAT) and superoxide dismutase (SOD), and reduced the MDA level. The reductions in mitochondrial membrane potential, DNA fragmentation, and caspase activation were also attenuated by QUER. These findings suggest that dietary QUER can protect HCT116 cells against DDVP-induced oxidative stress and apoptosis.